HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK TERHADAP OBESITAS PADA REMAJA DI SMA NEGERI 5 PEKANBARU - Mailani jihadi; Tuti Restuastuti; Yanti Ernalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACT Obesity is a multifactorial disease, caused by excessive accumulation of fat tissue, which can damage the health. Many factors can influence the occurrence of obesity, including age, sex, diet and physical activity. Diet is the way or the behavior of a person or group of people in choosing, using food ingredients in food consumption on a daily basis based on the type of food, amount of food and frequency of consumption. The aim of this study is to describe the characteristics of respondents by sex nutritional status, energy intake and macro-nutrients (carbohydrates, protein, fat) and physical activity in adolescents in SMAN 5 Pekanbaru. This research is an analytical study with cross sectional study design. The population studied were students of class X and XI SMAN 5 Pekanbaru obese with a sample size of 40 people and non-obese with a sample size of 40 people. This research instrument uses a measuring tape as a measuring tool and questionnaire. Results of the analysis of the number of respondents 80 people, consists of 30 men and 50 women. Based on the results obtained in the energy intake of 20 people declared quite tends risky adolescent obesity, based on macro nutrients mostly shows the macro nutrient intake (carbohydrate, protein, fat) fairly and in others a high intake of protein intake showed that in 20 (95.2 %) adolescents were high protein intake. Compared to non-obese adolescents showed 40 people had less energy intake. From the table 4.3 it can be seen that physical activity is less active significant association with obesity and physical activity are less active have a greater chance obese than students whose activities are more activeKey words : obesity; food pattern; activity pattern; adolescent